Sistem Informasi Ketersediaan Pangan Dengan Menggunakan Metode Fuzzy Tsukamoto Berbasis Android - azis, pandy; Ahmad Hanafie; Syarifuddin Baco (Ainet : Jurnal Informatika, 2024)
AbstractThe development of digital technology is developing rapidly nowadays, where almost all types of data and information processing are carried out using computers. This makes there are more and more data and information processing problems that must be resolved, such as preparing reports, to supporting decision making in a case, including the District Food Security Service. Pangkajene Islands. This type of research is quantitative research. The Pangkajene and Islands Regency Food Security Service was used as a research location between March and April 2023. Data collection techniques through literature reviews, interviews, observations, the Fuzzy Tsukamoto Algorithm are used in this food availability information system. Food Price Fluctuations using a data sampling system sourced from 3 (three) main markets, carrying out the function of monitoring food availability, intensively collaborating with the Department of Agriculture in terms of exchanging data. creating an information system to predict food availability based on Android. This information system provides ease of administration in storing and processing food availability information data for the past, present and future, making it easier for people involved in the field of food security to obtain data that can be viewed at any time , making it easier for people to get market prices related to food commodities, especially basic necessities at the Pangkep Food Security Service. Keyword: information Systems; food security; fuzzy tsukamoto